The Relationship Between Self-Concept, Role of Peers and Family Function and Adolescents’ Premarital Sexual Behavior - Rachmawati, Praba Diyan; Triharini, Mira; Salmahella, Dinda (International Journal of Psychosocial Rehabilitation, 2020)
The incidence of premarital sexual behavior in adolescents is still high in Indonesia. Premarital sexual behavior can be influenced by both internal and external factors. The purpose of this study was to analyze the relationship between self-concept, the role of peers and family function and adolescent premarital sexual behavior. The design of this study used a correlational cross-sectional approach. A total of 173 samples were taken and a purposive sampling technique was used. The independent variables in this study were self-concept, the role of peers and family function. The dependent variable was premarital sexual behavior. Data collection was done using a questionnaire and analyzed using Spearman’s Rho with significance level α = 0.05. The results of this study indicate that there was no relationship between self-concept and premarital sexual behavior (p=0.142), but there was a significant relationship between the roles of peers (p = 0.000) and family function (p=0.000) and premarital sexual behavior. Lower self-concept and family function in adolescents, the risk of having premarital sexual behavior, while the stronger the negative influence of peers also the higher the premarital sexual behavior. Further research is suggested to develop interventions with approaches to peers and adolescent families to prevent premarital sex.